Thermoplastic resin composition and molded article manufactured from the same
Patent Information
- Application Number
- KR1020230056574
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2043-04-28
Smart Images

Figure 112023048388123-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The invention relates to a thermoplastic resin composition and a molded article manufactured therefrom. Background Technology
[0002] Polycarbonate resin is a material widely used in the plastics industry as one of the engineering plastics.
[0003] Polycarbonate resins exhibit high heat resistance due to their bulk molecular structure, such as bisphenol-A, which causes the glass transition temperature (Tg) to reach approximately 150°C. Additionally, the carbonyl groups of the carbonate group have high rotational mobility, which imparts flexibility and rigidity to the polycarbonate resin. Furthermore, as an amorphous polymer, it has excellent transparency, impact resistance, and compatibility with other resins.
[0004] However, polycarbonate resin has the disadvantage of poor fluidity, so it is widely used in alloy form with various resins to compensate for workability and post-processing capabilities. Among these, polycarbonate / polyethylene terephthalate alloy resin exhibits excellent durability, moldability, heat resistance, and impact resistance, leading to its application in a wide range of fields including the electrical and electronics, automotive, construction, and other consumer materials. In particular, it is attracting attention as a material capable of replacing metal parts when used as an automotive exterior material.
[0005] However, polycarbonate / polyethylene terephthalate alloy resins have a problem in that they lack dimensional stability, making it difficult to completely replace metal parts used in automobiles. Accordingly, methods have been attempted to improve dimensional stability by reinforcing polycarbonate / polyethylene terephthalate alloy resins with mineral fillers; however, this method suffers from the problem of reduced impact resistance resulting from the reinforcement with mineral fillers.
[0006] To address the above problem, attempts have been made to add various impact modifiers to mineral filler-reinforced polycarbonate / polyethylene terephthalate alloy resins; however, while the use of impact modifiers improves impact strength, it leads to a problem where dimensional stability is reduced.
[0007] Therefore, in order to solve the aforementioned problems, it is necessary to develop a thermoplastic resin composition having excellent impact resistance and dimensional stability. The problem to be solved
[0008] The present invention provides a thermoplastic resin composition having excellent impact resistance and dimensional stability, and a molded article using the same. means of solving the problem
[0009] According to one embodiment, a thermoplastic resin composition is provided, comprising (A) 50 to 70 weight% of a polycarbonate resin; and (B) 30 to 50 weight% of a polyethylene terephthalate resin, with respect to 100 weight parts of a base resin, (C) 10 to 30 weight parts of a mineral filler; (D) 0.5 to 3 weight parts of a polyolefin-maleic anhydride graft copolymer; and (E) 1 to 5 weight parts of an ethylene-methyl acrylate copolymer, wherein the weight ratio of (D) the polyolefin-maleic anhydride graft copolymer to (E) the ethylene-methyl acrylate copolymer is 1:1 to 1:2.
[0010] The above (A) polycarbonate resin may have a melt flow index of 5 to 30 g / 10 min measured at 300°C and 1.2 kg weight according to ASTM D1238.
[0011] The above (B) polyethylene terephthalate resin may have an intrinsic viscosity of 0.7 to 1.5 dl / g as measured according to ASTM D4603.
[0012] The above (C) mineral filler may be in the form of fine particles or flakes.
[0013] The above (C) mineral filler may be any one of talc, mica, or a combination thereof.
[0014] The average particle size (D50) of the above (C) mineral filler may be 1 μm or more and 10 μm or less.
[0015] The above (D) polyolefin-maleic anhydride graft copolymer may comprise 95 to 99 weight% of substituted or unsubstituted polyolefin-derived components and 1 to 5 weight% of maleic anhydride-derived components based on the total weight of the above (D) polyolefin-maleic anhydride graft copolymer.
[0016] The above (E) ethylene-methyl acrylate copolymer may comprise 50 to 80 weight% of an ethylene-derived component and 20 to 50 weight% of a methyl acrylate-derived component based on the total weight of the above (E) ethylene-methyl acrylate copolymer.
[0017] The above thermoplastic resin composition may further include at least one additive selected from flame retardants, nucleating agents, coupling agents, glass fibers, plasticizers, lubricants, antibacterial agents, release agents, heat stabilizers, antioxidants, UV stabilizers, antistatic agents, pigments, and dyes.
[0018] Meanwhile, a molded article using a thermoplastic resin composition according to one embodiment may be provided.
[0019] The above-mentioned molded product may have a notched Izod impact strength of 8 kgf·cm / cm or more as measured according to ASTM D256 at a thickness of 1 / 8 inch.
[0020] The above molded product may have a total energy of 48 J or more in the drop impact strength evaluation measured by dropping a 5 kg weight from a height of 1 m onto a 3.2 mm thick flat plate specimen according to ASTM D1709. Effects of the invention
[0021] A thermoplastic resin composition according to one embodiment and a molded article using the same have excellent impact resistance and dimensional stability, so they can be widely applied to various uses, and in particular, they can be usefully applied to applications such as automotive exterior materials. Brief explanation of the drawing
[0022] Figure 1 shows specific criteria for determining the degree of impact resistance according to the fracture shape of the specimen in the evaluation of impact strength of a falling ball. Specific details for implementing the invention
[0023] Hereinafter, embodiments of the present invention will be described in detail. However, these are presented as examples and are not intended to limit the present invention, and the present invention is defined only by the appended claims.
[0024] According to one embodiment, a thermoplastic resin composition is provided comprising, for every 100 parts by weight of a base resin comprising (A) 50 to 70 weight% of a polycarbonate resin; and (B) 30 to 50 weight% of a polyethylene terephthalate resin, (C) 10 to 30 parts by weight of a mineral filler; (D) 0.5 to 3 parts by weight of a polyolefin-maleic anhydride graft copolymer; and (E) 1 to 5 parts by weight of an ethylene-methyl acrylate copolymer, wherein the weight ratio of (D) the polyolefin-maleic anhydride graft copolymer to (E) the ethylene-methyl acrylate copolymer is 1:1 to 1:2.
[0025] Hereinafter, each component included in the above thermoplastic resin composition will be described in detail.
[0026] (A) Polycarbonate resin
[0027] The above (A) polycarbonate resin is a polyester having carbonate bonds, and its type is not particularly limited; any polycarbonate resin available in the field of resin compositions may be used.
[0028] For example, it can be prepared by reacting a diphenol represented by the following chemical formula 1 with a compound selected from the group consisting of phosgene, halogen acid esters, carbonate esters, and combinations thereof.
[0029] [Chemical Formula 1]
[0030]
[0031] In the above chemical formula 1,
[0032] A is a linker selected from the group consisting of a single bond, a substituted or unsubstituted C1 to C30 alkylene group, a substituted or unsubstituted C2 to C5 alkenylene group, a substituted or unsubstituted C2 to C5 alkylidene group, a substituted or unsubstituted C1 to C30 haloalkylene group, a substituted or unsubstituted C5 to C6 cycloalkylene group, a substituted or unsubstituted C5 to C6 cycloalkenylene group, a substituted or unsubstituted C5 to C10 cycloalkylidene group, a substituted or unsubstituted C6 to C30 arylene group, a substituted or unsubstituted C1 to C20 alkoxylene group, a halogen acid ester group, a carbonate ester group, C=O, S, and SO2, and R 1 and R 2 Each is independently a substituted or unsubstituted C1 to C30 alkyl group or a substituted or unsubstituted C6 to C30 aryl group, and n1 and n2 are each independently integers from 0 to 4.
[0033] Two or more of the diphenols represented by the above chemical formula 1 may be combined to form repeating units of the polycarbonate resin.
[0034] Specific examples of the above diphenols include hydroquinone, resorcinol, 4,4'-dihydroxydiphenyl, 2,2-bis(4-hydroxyphenyl)propane (also known as 'Bisphenol-A'), 2,4-bis(4-hydroxyphenyl)-2-methylbutane, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(3-chloro-4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane, 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane, Examples include bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)ketone, bis(4-hydroxyphenyl)ether, etc. Among the above diphenols, preferably 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane, or 1,1-bis(4-hydroxyphenyl)cyclohexane may be used. More preferably, 2,2-bis(4-hydroxyphenyl)propane may be used.
[0035] The above (A) polycarbonate resin may be a mixture of copolymers prepared from two or more types of diphenols. In addition, the above polycarbonate resin may be a linear polycarbonate resin, a branched polycarbonate resin, a polyester carbonate copolymer resin, etc.
[0036] A specific example of the above linear polycarbonate resin is a bisphenol-A-based polycarbonate resin. A specific example of the above branched polycarbonate resin is a resin prepared by reacting a polyfunctional aromatic compound, such as trimellitic anhydride or trimellitic acid, with diphenols and carbonates. The above polyester carbonate copolymer resin can be prepared by reacting a difunctional carboxylic acid with diphenols and carbonates, and the carbonate used here may be a diaryl carbonate such as diphenyl carbonate or ethylene carbonate.
[0037] The above (A) polycarbonate resin may have a weight-average molecular weight of 10,000 to 200,000 g / mol, for example, 14,000 to 50,000 g / mol. When the weight-average molecular weight of the above (A) polycarbonate resin is within the above range, excellent impact resistance and fluidity can be obtained.
[0038] The above (A) polycarbonate resin may be included in an amount of 50 to 70 weight% with respect to 100 weight% of a base resin comprising (A) polycarbonate resin and (B) polyethylene terephthalate resin, for example, 50 to 60 weight%, for example, 60 to 70 weight%. In the above weight range, the thermoplastic resin composition may exhibit excellent appearance characteristics and mechanical strength.
[0039] The above (A) polycarbonate resin may have a melt flow index of 5 to 30 g / 10 min, e.g. 5 to 25 g / 10 min, e.g. 5 to 20 g / 10 min, measured at 300°C and 1.2 kg weight according to ASTM D1238. When the melt flow index of the above (A) polycarbonate resin is within the above range, it may exhibit excellent moldability and excellent impact resistance.
[0040] Meanwhile, the above (A) polycarbonate resin may be used by mixing two or more polycarbonate resins with different weight-average molecular weights or melt flow indices. By mixing and using polycarbonate resins with different weight-average molecular weights or melt flow indices, it is easy to control the thermoplastic resin composition to have the desired fluidity.
[0041] (B) Polyethylene terephthalate resin
[0042] The above (B) polyethylene terephthalate resin can impart excellent chemical resistance, fluidity, and moldability to the thermoplastic resin composition.
[0043] The above (B) polyethylene terephthalate resin may be a resin obtained by a polycondensation reaction from terephthalic acid or its derivative and ethylene glycol or its derivative, and may include polyethylene terephthalate (PET), glycol-modified polyethylene terephthalate (PETG), polytetramethylene glycol (PTMG), polypropylene glycol (PPG), copolymers of aliphatic polyester or aliphatic polyamide and polyethylene terephthalate (PET), and combinations thereof.
[0044] In addition, the above (B) polyethylene terephthalate resin may be a recycled polyethylene terephthalate resin recycled from waste polyethylene terephthalate resin. Here, the above waste polyethylene terephthalate resin refers to polyethylene terephthalate resin that has been used, such as waste PET bottles, and may be a waste polyethylene terephthalate resin that has been used one or more times.
[0045] The above (B) polyethylene terephthalate resin may have an intrinsic viscosity of 0.7 to 1.5 dl / g as measured according to ASTM D4603 in order to sufficiently ensure the impact resistance of the molded article using the thermoplastic resin composition.
[0046] According to one embodiment, the polyethylene terephthalate resin (B) may be included in an amount of 30 to 50 weight% with respect to 100 weight% of the base resin, for example, in an amount of 30 to 40 weight%. By including the polyethylene terephthalate resin within the above range, the thermoplastic resin composition has excellent chemical resistance, fluidity, and moldability.
[0047] (C) Mineral filler
[0048] In one embodiment, (C) the mineral filler can improve the dimensional stability of the thermoplastic resin composition.
[0049] The above (C) mineral filler may be, for example, in the form of fine particles or flakes.
[0050] As the above (C) mineral filler, mica, quartz powder, titanium dioxide, silicate, aluminosilicate, chalk, wollastonite, mica, layered clay, montmorillonite (especially ion-exchange modified chin-organo form montmorillonite), talc, kaolin, zeolite, vermiculite, aluminum oxide, silica, magnesium hydroxide, aluminum hydroxide, glass flakes, etc. may be used, and a mixture of different mineral fillers may also be used.
[0051] In one embodiment, the mineral filler (C) may be any one of talc, mica, and combinations thereof, and preferably may be talc.
[0052] The average particle size of the above (C) mineral filler may be 1 μm or more, e.g., 2 μm or more, e.g., 3 μm or more, e.g., 5 μm or more, e.g., 7 μm or more, as the median value (D50) of the cumulative particle size distribution curve measured according to ISO 13320-1 using a particle size analyzer using laser diffraction (e.g., a particle size analyzer of Malvern Panalytical), e.g., 10 μm or less, e.g., 8 μm or less, e.g., 5 μm or less, e.g., 4 μm or less, e.g., 1 to 6 μm, e.g., 2 to 5 μm. Within the above average particle size range, the mechanical strength and appearance of the molded article using the thermoplastic resin composition may be excellent.
[0053] The above (C) mineral filler may be included in an amount of 10 to 30 parts by weight, for example, 10 to 20 parts by weight, per 100 parts by weight of the base resin. In the above weight range, the dimensional stability, heat resistance, mechanical strength, and appearance of the thermoplastic resin composition containing the above (C) mineral filler and the molded article using the same may be excellent.
[0054] (D) Polyolefin-maleic anhydride graft copolymer
[0055] In one embodiment, (D) a polyolefin-maleic anhydride graft copolymer is used together with (E) an ethylene-methyl acrylate copolymer described later to impart excellent impact resistance and appearance properties to the thermoplastic resin composition.
[0056] In one embodiment, the (D) polyolefin-maleic anhydride graft copolymer may be one in which maleic anhydride is grafted onto a substituted or unsubstituted polyolefin main chain.
[0057] Examples of olefins constituting the above substituted or unsubstituted polyolefins include ethylene, propylene, 1-butene, isobutylene, 2-butene, cyclobutene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 3-methyl-1-butene, 4-methyl-1-butene, cyclopentene, 1-hexene, cyclohexene, 1-octene, 1-decene, and 1-dodecene, or combinations thereof.
[0058] In one embodiment, the (D) polyolefin-maleic anhydride graft copolymer may comprise 95 to 99 weight% of a substituted or unsubstituted polyolefin-derived component and 1 to 5 weight% of a maleic anhydride-derived component based on the total weight of the (D) polyolefin-maleic anhydride graft copolymer.
[0059] The above (D) polyolefin-maleic anhydride graft copolymer may be included in an amount of 0.5 to 3 parts by weight, for example 1 to 3 parts by weight, for example 1 to 2 parts by weight, for example 2 to 3 parts by weight, with respect to 100 parts by weight of the base resin. When the content of the above (D) polyolefin-maleic anhydride graft copolymer satisfies the aforementioned range, the thermoplastic resin composition and the molded article made therefrom may exhibit excellent impact resistance and compatibility.
[0060] (E) Ethylene-methyl acrylate copolymer
[0061] In one embodiment, (E) an ethylene-methyl acrylate copolymer is used together with the (D) polyolefin-maleic anhydride graft copolymer to impart excellent impact resistance and appearance properties to the thermoplastic resin composition.
[0062] The above (E) ethylene-methyl acrylate copolymer may comprise 50 to 80 weight% of an ethylene-derived component and 20 to 50 weight% of a methyl acrylate-derived component based on the total weight of the above (E) ethylene-methyl acrylate copolymer.
[0063] According to one embodiment, the ethylene-methyl acrylate copolymer (E) may be included in an amount of 1 to 5 parts by weight, for example 2 to 3 parts by weight, per 100 parts by weight of the base resin. In the above weight range, the impact resistance of the thermoplastic resin composition may be even better.
[0064] In one embodiment, the weight ratio of the (D) polyolefin-maleic anhydride graft copolymer to the (E) ethylene-methyl acrylate copolymer may be 1:1 to 1:2. When the components are included within the above weight ratio range, the impact resistance of the thermoplastic resin composition and the molded article made therefrom may be even better.
[0065] (F) Other additives
[0066] In addition to the above components (A) to (E), the thermoplastic resin composition according to one embodiment may further include one or more additives necessary for balancing the properties under conditions that maintain excellent impact resistance, dimensional stability, etc., or depending on the final use of the thermoplastic resin composition.
[0067] Specifically, the above additives may include flame retardants, nucleating agents, coupling agents, glass fibers, plasticizers, lubricants, antibacterial agents, release agents, heat stabilizers, antioxidants, UV stabilizers, antistatic agents, pigments, dyes, etc., and these may be used alone or in combination of two or more.
[0068] These additives may be appropriately included within a range that does not impair the physical properties of the thermoplastic resin composition, and may be included in an amount of 20 parts by weight or less per 100 parts by weight of the base resin, but are not limited thereto.
[0069] The thermoplastic resin composition according to the present invention can be manufactured by a known method for manufacturing a thermoplastic resin composition.
[0070] For example, the thermoplastic resin composition according to the present invention can be manufactured in the form of pellets by mixing the components of the present invention and other additives, and then melting and kneading them using an extruder.
[0071] A molded article according to one embodiment of the present invention can be manufactured from the thermoplastic resin composition described above.
[0072] The above-mentioned molded product may have a notched Izod impact strength of 8 kgf·cm / cm or more as measured according to ASTM D256 at a thickness of 1 / 8 inch.
[0073] The above molded product may have a total energy of 48 J or more in the drop impact strength evaluation measured by dropping a 5 kg weight from a height of 1 m onto a 3.2 mm thick flat plate specimen according to ASTM D1709.
[0074] The present invention will be explained in more detail below through examples and comparative examples, but the following examples and comparative examples are for illustrative purposes only and are not intended to limit the invention.
[0075] Examples 1 to 4 and Comparative Examples 1 to 4
[0076] The thermoplastic resin compositions of Examples 1 to 4 and Comparative Examples 1 to 4 were prepared according to the component content ratios listed in Table 1 below.
[0077] The components listed in Table 1 were dry-mixed and quantitatively fed continuously into the feed section of a twin-screw extruder (L / D = 29, diameter = 45 mm) for melting and kneading. At this time, the barrel temperature of the twin-screw extruder was set to approximately 250°C. Subsequently, the thermoplastic resin composition pelletized through the twin-screw extruder was dried at approximately 100°C for approximately 2 hours, and then a specimen for measuring physical properties was injection-molded using a 6 oz injection molding machine with a cylinder temperature of approximately 270°C and a mold temperature of approximately 60°C.
[0078] In Table 1, (A) and (B) represent the weight percentage of each component in 100 weight% of the base resin, and (C) to (E) represent the weight percentages relative to 100 weight parts of the base resin ((A)+(B)).
[0079] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 (A) 65 65 65 65 65 65 65 65 (B) 35 35 35 35 35 35 35 35 (C) 20 20 20 10 20 20 20 40 (D) 1 2 1 1 2 1 2 1 (E) 2 2 1.5 2 - 3 1 2
[0080] The description of each component listed in Table 1 above is as follows.
[0081] (A) Polycarbonate resin
[0082] Bisphenol-A-based polycarbonate resin (Lotte Chemical Co., Ltd.) having a melt flow index of approximately 18 g / 10 min measured at 300°C and 1.2 kg weight according to ASTM D1238
[0083] (B) Polyethylene terephthalate resin
[0084] Polyethylene terephthalate resin with an intrinsic viscosity of approximately 1.2 dl / g as measured according to ASTM D4603 (Lotte Chemical Co.)
[0085] (C) Mineral filler
[0086] Talc with a median (D50) of approximately 4.4 μm on the cumulative particle size distribution curve measured according to ISO 13320-1 (IMERYS, JETFINE 3CA)
[0087] (D) Polyolefin-maleic anhydride graft copolymer
[0088] Polyethylene-maleic anhydride graft copolymer containing approximately 1.3 wt% of maleic anhydride-derived components (Lotte Chemical, EM-101)
[0089] (E) Ethylene-methyl acrylate copolymer
[0090] Ethylene-methyl acrylate copolymer containing approximately 24 wt% methyl acrylate-derived components (DOW, AC 12024)
[0092] Experimental Example
[0093] The experimental results are shown in Table 2 below.
[0094] (1) Impact resistance (unit: kgf·cm / cm): Notched Izod impact strength was measured at room temperature (about 23℃) according to ASTM D256 for a 1 / 8 inch thick specimen.
[0095] (2) Dimensional stability (unit: μm / m·℃): According to ASTM E831, a specimen with dimensions of 6 mm x 12 mm x 10 mm (width x length x height) was tested in the resin flow direction (width direction) using a thermomechanical analyzer (TA Instruments, Q400). After stress relief in the range of -50℃ to 130℃, the coefficient of linear expansion in the resin flow direction of the specimen was measured in the temperature range of -30℃ to 30℃. It was determined that the lower the coefficient of linear expansion, the better the dimensional stability.
[0096] (3) Practical impact resistance (Unit: J): According to ASTM D1709, the total energy at the time of specimen fracture was measured by evaluating the falling dart impact (FDI) by dropping a 5 kg dart from a height of 1 m onto a 3.2 mm thick flat plate specimen. After the evaluation, the degree of impact resistance was determined by visually observing the fracture shape of the specimen. Specific criteria for determining the degree of impact resistance based on the fracture shape of the specimen in the falling dart impact evaluation are shown in Figure 1. As shown in Figure 1, the evaluation was O if the specimen did not break and only deformed after the weight drop, △ if it broke slightly, and × if it broke completely into pieces.
[0097] unit Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Izod impact strength ㎏f·㎝ / ㎝ 9 10 8 20 5 9 6 3 coefficient of linear expansion μm / m·℃ 43 44 41 52 40 46 42 35 degree of impact from falling ball and city shock - O O O O △ O △ × Falling ball shock, market capitalization, energy J 48 48 48 48 38 48 40 20
[0098] From Tables 1 and 2 above, it can be seen that by using polycarbonate resin, polyethylene terephthalate resin, mineral filler, polyolefin-maleic anhydride graft copolymer, and ethylene-methyl acrylate copolymer in optimal amounts, a thermoplastic resin composition with excellent impact resistance and dimensional stability and a molded article using the same can be realized.
[0099] In particular, when evaluating the impact strength of a falling ball in the present embodiment, ductile fracture occurs in which the specimen undergoes only deformation without breaking, whereas in Comparative Examples 1, 3, and 4, brittle fracture occurs in which the specimen breaks or fragments. These results indicate that the impact resistance of a thermoplastic resin composition and a molded article produced therefrom can be particularly improved by including the above components within a specific range, and in particular by including a weight ratio of polyolefin-maleic anhydride graft copolymer and ethylene-methyl acrylate copolymer in a ratio of 1:1 to 1:2.
[0100] Although the present invention has been described above through preferred embodiments as previously described, those skilled in the art will readily understand that the present invention is not limited thereto and that various modifications and variations are possible without departing from the concept and scope of the claims set forth below.
Claims
Claim 1 A thermoplastic resin composition comprising, for every 100 parts by weight of a base resin comprising (A) 50 to 70 weight% of a polycarbonate resin; and (B) 30 to 50 weight% of a polyethylene terephthalate resin, (C) 10 to 30 parts by weight of a mineral filler; (D) 0.5 to 3 parts by weight of a polyolefin-maleic anhydride graft copolymer; and (E) 1 to 5 parts by weight of an ethylene-methyl acrylate copolymer, wherein the weight ratio of (D) the polyolefin-maleic anhydride graft copolymer to (E) the ethylene-methyl acrylate copolymer is 1:1 to 1:
2. Claim 2 In claim 1, the above (A) polycarbonate resin is a thermoplastic resin composition having a melt flow index of 5 to 30 g / 10 min measured at 300°C and 1.2 kg weight conditions according to ASTM D1238. Claim 3 In claim 1, the above (B) polyethylene terephthalate resin is a thermoplastic resin composition having an intrinsic viscosity of 0.7 to 1.5 dl / g as measured according to ASTM D4603. Claim 4 In claim 1, the above (C) mineral filler is a thermoplastic resin composition in the form of fine particles or flakes. Claim 5 In claim 1, the above (C) mineral filler is a thermoplastic resin composition, which is any one of talc, mica, and a combination thereof. Claim 6 A thermoplastic resin composition according to claim 1, wherein the average particle size (D50) of the (C) mineral filler is 1 μm or more and 10 μm or less. Claim 7 A thermoplastic resin composition according to claim 1, wherein the (D) polyolefin-maleic anhydride graft copolymer comprises 95 to 99 weight% of a substituted or unsubstituted polyolefin-derived component and 1 to 5 weight% of a maleic anhydride-derived component based on the total weight of the polyolefin-maleic anhydride graft copolymer. Claim 8 A thermoplastic resin composition according to claim 1, wherein the (E) ethylene-methyl acrylate copolymer comprises 50 to 80 weight% of an ethylene-derived component and 20 to 50 weight% of a methyl acrylate-derived component based on the total weight of the ethylene-methyl acrylate copolymer. Claim 9 A thermoplastic resin composition according to claim 1, further comprising at least one additive selected from flame retardants, nucleating agents, coupling agents, glass fibers, plasticizers, lubricants, antibacterial agents, release agents, heat stabilizers, antioxidants, UV stabilizers, antistatic agents, pigments, and dyes. Claim 10 A molded article using a thermoplastic resin composition according to any one of claims 1 to 9. Claim 11 In paragraph 10, the above-mentioned molded article is a molded article having a notched Izod impact strength of 8 kgf·cm / cm or more as measured according to ASTM D256 at a thickness of 1 / 8 inch. Claim 12 In claim 10, the above-mentioned molded article is a molded article having a total energy of 48 J or more in the drop ball impact strength evaluation measured by dropping a 5 kg weight from a height of 1 m onto a 3.2 mm thick flat plate specimen according to ASTM D1709.
Citation Information
Patent Citations
Thermoplastic polyester composition having improved impact resistance
JP2001181485A
Method for preparing polyester / polycarbonate blend with advanced color stability
KR1020090008825A
Thermoplastic resin composition
KR1020100072804A
Polycarbonate resin composition and article comprising the same
KR1020160081806A
